Economic development in twentieth century East Asia : the international context - Ikeo, Aiko, 1956- (Routledge studies in the growth economies of Asia., 1997)
This collection supplies fascinating insights into aspects of East Asian economic development. It will interest scholars in a variety of related fields and provoke further research and debate.